Weed management module for Indian mustard (Brassica juncea L.) - Swati Dash; Anil Shukla (Journal of Oilseed Brassica, 2026)
A field experiment was conducted at Govind Ballabh Pant University of Agriculture & Technology, Pantnagar duringrabi season of 2019-20 for exploration of weed management module for Indian mustard (Brassica juncea L.). The thirteentreatment combinations of different weedicides and their application rates along with weedy check (control) wereaccommodated in randomized complete block design with three replications. The maximum values of yield attributingcharacters i.e. number of branches per plant, number of siliquae/plant, seed weight per plant seed yield was obtainedwith application of pendimethalin @ 1.0 kg a.i./ha (PE) + hand weeding (HW) at 30 days after sowing (DAS). Pendimethalin@ 1.0 kg a.i./ha (PE) + HW) at 30 DAS also recorded the maximum weed control efficiency, seed yield and B:C ratio overthe other treatments.